Eksistensi Pemberian Uang Kompensasi atas Selesainya Kontrak Kerja di Perusahaan - Masnun Masnun; Asri Wijayanti; Fajar Rachmad Dwi Miarsa; Ahmad Heru Romadhon (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2025)
The purpose of writing this article is that workers who have an employment relationship based on a Fixed-Term Employment Agreement (PKWT) have the right to receive compensation money in accordance with legal provisions. The research method used is juridical-normative, which involves legal research by examining regulations and literature study (secondary sources). The form of legal protection for workers (Indonesian Migrant Workers and/or Foreign Workers) regarding the provision of compensation upon the completion of the work contract in the Company based on the employment relationship under the Fixed-Term Employment Agreement (PKWT) in accordance with Article 61A of Law No. 6/2023 concerning Job Creation Law and Article 15 of Government Regulation 35/2021 concerning Fixed-Term Employment Agreements, Outsourcing, Working Hours and Rest Periods, and Termination of Employment is to require companies to provide monetary compensation to workers/laborers whose employment relationship is based on PKWT. The nominal amount of compensation is proportionally based on the duration of the employment relationship that has been carried out (Articles 15-16; 47 PP 35/2021 in conjunction with Article 80 point 15 UU 6/2023). Violations for non-payment of compensation money are administrative sanctions, including written warnings, business activity restrictions, temporary cessation of part or all production equipment, and business activity freezing. (Article 61 PP 35/2021). The legal recourse that can be taken if a worker does not receive compensation for the completion of their work contract at the company is that the worker can file a lawsuit with the Industrial Relations Court (Article 81 of Law 2/2004 on the Settlement of Industrial Relations Disputes/PPHI)